2015
DOI: 10.1007/s10943-015-0005-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of a Spiritual Support Subscale for the MOS Social Support Survey

Abstract: While spirituality and religious practices are important in coping with illness or other crises, there are few ways of assessing support that people receive from members of their spiritual communities. The goal of this study was to validate a new spiritual support subscale for the Medical Outcomes Study Social Support scale (MOS-SSS). Questions for the subscale were formed based on responses of 135 breast cancer survivors who were interviewed about their cancer experience. Exploratory factor analysis resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Thirty‐two studies tested internal consistency reliabilities using Cronbach alpha; one study calculates item reliability using Rasch analysis (Kim et al, 2017). Thirty‐one studies reported sufficient internal consistency reliabilities (higher than a desirable value of 0.70), and two studies had a subscale of the MOS‐SSS with Cronbach's alpha slightly lower than the desirable value (0.61–0.65 vs. 0.70) (Levine et al, 2015; Norhayati et al, 2015). Three studies reported overall internal consistency reliabilities but not internal consistency reliabilities for all subscales of the measurement (Gjesfjeld et al, 2008; Mahmud et al, 2004; Margolis et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐two studies tested internal consistency reliabilities using Cronbach alpha; one study calculates item reliability using Rasch analysis (Kim et al, 2017). Thirty‐one studies reported sufficient internal consistency reliabilities (higher than a desirable value of 0.70), and two studies had a subscale of the MOS‐SSS with Cronbach's alpha slightly lower than the desirable value (0.61–0.65 vs. 0.70) (Levine et al, 2015; Norhayati et al, 2015). Three studies reported overall internal consistency reliabilities but not internal consistency reliabilities for all subscales of the measurement (Gjesfjeld et al, 2008; Mahmud et al, 2004; Margolis et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Spiritual support. Spiritual support was measured using the spiritual support subscale of the MOS Social Support Survey [58]. This subscale consists of three 5-point Likert-type scale items with the anchors (1) strongly disagree and strongly agree (5), including "Whenever I need it, there is someone I can talk to about spiritual matters", and "Whenever I need help, there is someone who will pray for me (or meditate with me)".…”
Section: Methodsmentioning
confidence: 99%
“…However, the findings from several previous studies suggest that spiritual support may play an important stress-buffering role for faith-based community members [54][55][56]. Recent scholars have conceptualized spiritual support as perceived support from other faith-based community members and spiritual leaders regarding spiritual matters [57,58]. Seeking spiritual support has been identified as way that many faith-based community members have coped with other major crisis events in the past, such as 11 September [59].…”
Section: Buffering Model Of Social Support and Types/sources Of Suppo...mentioning
confidence: 99%